2004
DOI: 10.1210/me.2004-0087
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Pituitary Tumor Apoptosis Gene

Abstract: To determine mechanisms for pituitary neoplasia we used methylation-sensitive arbitrarily primed-PCR to isolate novel genes that are differentially methylated relative to normal pituitary. We report the isolation of a novel differentially methylated chromosome 22 CpG island-associated gene (C22orf3). Sodium bisulfite sequencing of pooled tumor cohorts, used in the isolation of this gene, showed that only a proportion of the adenomas within the pools were methylated; however, expression analysis by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…The growth suppressive properties of this gene, in a pituitary context, were investigated in vitro; transfection of GADD45g significantly reduced tumour cell line proliferation as determined by colony-forming efficiency (CFE) assays. Similar conclusions, with respect to reduced expression of GADD45g, in a significant proportion of pituitary tumours were reached in an independent study (Bahar et al 2004b). This study also investigated the mechanisms responsible for or associated with loss of transcript expression and showed that loss of GADD45g expression was significantly associated with methylation of this gene CpG island.…”
Section: Gadd45gsupporting
confidence: 83%
See 1 more Smart Citation
“…The growth suppressive properties of this gene, in a pituitary context, were investigated in vitro; transfection of GADD45g significantly reduced tumour cell line proliferation as determined by colony-forming efficiency (CFE) assays. Similar conclusions, with respect to reduced expression of GADD45g, in a significant proportion of pituitary tumours were reached in an independent study (Bahar et al 2004b). This study also investigated the mechanisms responsible for or associated with loss of transcript expression and showed that loss of GADD45g expression was significantly associated with methylation of this gene CpG island.…”
Section: Gadd45gsupporting
confidence: 83%
“…Interestingly, the murine homologue of this gene is not expressed in the mouse pituitary cell line AtT20 and the CpG island associated with murine GADD45g is also heavily methylated. Treatment of these cells with the demethylating agent 5-Aza 2 0 -deoxycytodine resulted in robust re-expression of this gene (Bahar et al 2004b). It is important to note that these findings do not show that methylation per se is responsible for gene silencing; however, they do show this change is causal in maintaining the silent epigenetic state.…”
Section: Gadd45gmentioning
confidence: 78%
“…cDNA was synthesized using 200U of Maloney mouse leukemia virus reverse transcriptase (Promega, Southampton, UK) according to the manufacturer's instructions and as previously described. [26] Quantitative RT-PCR:…”
Section: Stem-loop Rt-pcrmentioning
confidence: 99%
“…These techniques would permit, for the first time, the whole genome analysis for identification of novel methylated genes (reviewed in Esteller (2007)). Indeed, our own studies exploiting methylationsensitive digestion and subsequent PCR were successful at identifying novel and inappropriately methylated genes in pituitary adenomas (Bahar et al 2004). However, a concern with these types of studies is that the majority of techniques rely on methylation-sensitive restriction digest, where incomplete digestion can confound the interpretation of derived data.…”
Section: Detecting Epigenetic Change Dna Methylationmentioning
confidence: 99%